2019
DOI: 10.1002/pro.3648
|View full text |Cite
|
Sign up to set email alerts
|

Sequence composition versus sequence order in the cryoprotective function of an intrinsically disordered stress‐response protein

Abstract: Intrinsically disordered stress proteins have been shown to act as chaperones, protecting proteins from damage caused by stresses such as freezing and thawing. Dehydration proteins (dehydrins) are intrinsically disordered stress proteins that are found in almost all land plants. They consist of a variable number of the short, semi-conserved, Y-, S-, and K-segments, with longer stretches of poorly conserved sequences in between. Previous studies have provided conflicting views on the details of the dehydrin cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…The examples include N-terminal disordered peptides derived from bovine prion protein precursor (bPrP), PrP (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and PrP(108-119) 38 . However, we did not find any sequence similarity among IDP-D10, PrP (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), or PrP(108-119). Notably, IDP-D10 is a partial sequence of TNFRSF11B, which, www.nature.com/scientificreports/ unlike bPrP, is not expressed in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The examples include N-terminal disordered peptides derived from bovine prion protein precursor (bPrP), PrP (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and PrP(108-119) 38 . However, we did not find any sequence similarity among IDP-D10, PrP (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), or PrP(108-119). Notably, IDP-D10 is a partial sequence of TNFRSF11B, which, www.nature.com/scientificreports/ unlike bPrP, is not expressed in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular shielding may decrease stochastic self-collisions between target enzyme molecules during the occasional high concentrations occurring in repeated freeze–thaw cycles 21 . Two research groups have reported that a weak but clear correlation between the cryoprotective activity of various DHN segments and their mutants versus their hydrodynamic radius (Rh), whereas their amino acid compositions or sequences were not relevant 21 , 26 , 28 , 29 . We succeeded in expanding the concept of the molecular shield by showing that it is independent of the amino acid sequence and only depends on the intrinsic disorder of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…25,26,28 In vitro , LEA proteins protect LDH, fumarase, and citrate synthase activity and inhibit the latter’s aggregation. 24,26,28,50,62,64,65 Additionally, formulation with LEA proteins reduces the loss of fluorescence of the red fluorescent protein mCherry upon vacuum-drying and rehydration. 26…”
Section: Additives and Protection From Vacuum-drying Stressmentioning
confidence: 99%
“…It has been observed that the cryoprotective capacity of DHNs depends on the size (hydrodynamic radius) and the intrisic disorder, highlighting the importance of the composition and size of the Phi segments, which are generally less conserved than the structural motifs 61 . It has been also demonstrated that it is the size and sequence composition of DHNs that is the most important for preventing aggregation, while for freeze damage it is the sequence composition that is most significant 62 . Thus, it seems that the simple presence of K and S segments would not be necessarily good predictors of the functional characteristics of DHNs.…”
Section: Discussionmentioning
confidence: 99%